2016
DOI: 10.26719/2016.22.11.817
|View full text |Cite
|
Sign up to set email alerts
|

Psychobehavioural responses to the 2014 Middle East respiratory syndrome-novel corona virus (MERS CoV) among adults in two shopping malls in Jeddah, western Saudi Arabia

Abstract: Sporadic cases of Middle East respiratory syndrome caused by a novel corona virus (MERS-CoV) were first detected in Saudi Arabia in June 2012. The number of cases was highest during April and May 2014. To assess determinants of psychobehavioural responses among the general population in Jeddah, western Saudi Arabia, a cross-sectional survey was conducted at the end of June 2014. Data included sociodemographic characteristics, level of anxiety, protective measures and social avoidance responses. A total of 358 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 29 publications
10
59
1
1
Order By: Relevance
“…The preventive measures are being practiced at home and in the hospital whereby the respondents are confident that they may not contract MERS-CoV disease. The findings of this study coincide with the study of Alnajjar et al [19] which stipulated that anxiety level was significantly associated with increased perception of susceptibility to infection and that clinical prevention was modest. Similar to the findings of Aldrees et.…”
Section: Knowledge and Perception Of Allied Health Practitioners Towasupporting
confidence: 79%
“…The preventive measures are being practiced at home and in the hospital whereby the respondents are confident that they may not contract MERS-CoV disease. The findings of this study coincide with the study of Alnajjar et al [19] which stipulated that anxiety level was significantly associated with increased perception of susceptibility to infection and that clinical prevention was modest. Similar to the findings of Aldrees et.…”
Section: Knowledge and Perception Of Allied Health Practitioners Towasupporting
confidence: 79%
“…Despite heightened anxiety and depression in facing the COVID‐19 outbreak, this study revealed that less than 2% of the respondents indicated that they wanted to take leave from work or would choose to avoid duties. This proportion is less than that reported in a study of nurses who would take a leave to avoid infection (4.3%) (AlNajjar et al, 2016). It seems that professional commitment overrides their fear of contagion.…”
Section: Discussioncontrasting
confidence: 54%
“…Levels of anxiety and depression are often related to one’s thinking and appraisal of COVID‐19. Nurses who were more worried that they may contract the virus had escalated psychological responses, as documented in a Middle East respiratory syndrome coronavirus (MERS‐CoV) study (AlNajjar, Attar, Faraha, & AlThaqafi, 2016; Kim & Choi, 2016; Oh et al, 2017), an influenza A(H1N1) study (Cowling et al, 2010), and SARS studies (Chen et al, 2006; Maunder et al, 2003). The current study found that over 50% of nurses felt that it was quite possible for them or others to contract COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…Several pandemic‐related behaviours were identified and categorized into protective behaviours (Al Najjar et al . 2016; Bults et al . 2011; Cowling et al .…”
Section: Resultsmentioning
confidence: 99%